Fluxograma de apoio à tomada de decisões para assistência de enfermagem à pessoa em sofrimento psíquico na atenção básica - Mesquita, Keysse Suélen Fidelis de (2016)
This study aimed to propose the formulation of a supportive flowchart on decision-making of nurses from basic care for management or reference of people on psychological pain. It is a two phases research: phase I – Descriptive and explorative study with a qualitative nature, developed into two stages, one, it is a field research for the execution of interviews and the other, it is an integrative review of the literature for survey of scientific publications about the focused subject-matter. Phase II – methodological study to develop a flowchart to support nurse decision-making, following the stages of planning and consulting the flowchart by specialists. The field study had as participants 16 nurses from Unities of Basic Care and Unities of Family Care. To them were applied semi-structured interviews conducted with the support of a semi-structured script on Jun of 2015 at the performance unities of the nurses, and they validated the transcriptions on July and August of 2015. The testimonies were analyzed according to the Content Thematic analysis of Minayo, which made to appear two categories: organization of the work process and understanding on psychological distress, and five subcategories: attendance dynamic to a person on psychological distress; nurse actions before a person on psychological distress; difficulties and strategies for achievement of the assistance to a person on psychological distress; psychological distress concept; and the identification psychological distress signals and symptoms. Through those subcategories and the integrative review, necessary items were brought up to the formulation of the flowchart suggested. The Flowchart Reference Merhy Analyzer with adaptations was used on the study to prepare the suggested flowchart. Regarding the content, dimensions, flux and the flowchart structure, the study took as the base and flowchart source of spontaneous demand attendance created by Ministry of Health in 2012, along with its data were added identified items on the two first stages (PHASE I). Starting from the combination of this information, it was obtained the version I of the flowchart (PHASE II), which underwent through two consecutives consultations of experts of mental health, by the Delphi method. The tool prepared could offer ampleness of an entire process on nursing assistance and to be a facilitator in care management, as provides the nurse subsidy on the most appropriate decision-making, agile and safer, avoiding gaps and failures in assistance of a person in psychic suffering.